THE EFFICIENCY WATER CLARIFICATION IN MODELS OF VERTICAL TANK - Yakovlіev V. S.; Voinarovskyi, B. A. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The purpose of this article is to analyze theoretical and experimental data on the structures and analyze the performance of type clarifier, as well as to highlight the shortcomings of the proposed designs. It was found that for the experiments it is necessary to create a physical model of the vertical sediment tank in the laboratory using the following factors: material costs, technological parameters, design parameters. The purpose of this article is to show the effect of the velocity of upward flow of water inside the vertical settler on the efficiency of its lighting on the physical model of the vertical sediment tank. There are mathematical dependences of turbidity of clarified water as well as the efficiency of water clarification from the turbidity of the incoming water for different speed values in the lighting area of the vertical sediment tank. It was established the use of the calculations required area lighting area, vertical settling tanks, water speed, cleansing of water without efficiency loss, which leads to significant savings in capital investments.